A simple and portable instrument for determination of captopril in pharmaceutical formulations - Ribeiro, Paulo Roberto da Silva; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP]; Tubino, Matthieu (My University, 2014)
Objective: This article describes the application and the performance of a cheap, simple and portable device that can be used for colorimetric quantitative determination of captopril (CPT) in pharmaceutical preparations. Methods: The sensor is a light detector resistor (LDR) placed into a black PTFE cell and coupled to a low cost multimeter (Ohmmeter). The instrument has been tested and is easy and fast to use. The quantitative study is based mainly on reduction of ammonium molybdate by captopril, in the presence of sulphuric acid, producing a green-yellow compound (max 407 nm). The calibration curves were obtained by plotting the electric resistance of the LDR against the CPT concentration on the range of 4.60 x 10-4 to 1.84 x 10-3 mol l-1 with a good coefficient of determination (R2 = 0.9962). Results: Statistical analysis of the obtained results showed no significant difference between the proposed methodology and the official reported method as evident from the t-test and variance ratio at 95% confidence level. Conclusion: The results of this study demonstrate that the instrument can be used for simple, accurate, precise, fast, in situ and low-cost colorimetric analysis of captopril in pharmaceuticals products.
Keywords: Captopril; Optical sensor; Pharmaceuticals formulations; Quality control; Resistance measurements